#TITLE_ALTERNATIVE# - ABDUL ROHMAN (NIM 15108007); Pembimbing: Dr. rer. nat. Wiwin Windupranata, ST., M.Si. dan Dr. , IRWAN
As an archipelagic country, most of Indonesian people live along the coastal area. Coastal is a transition area between land ecosystem and the marine ecosystem. It connect each other and have a various characteristic at different places. This interaction affect to the coastal area condition, as an example is the coastal erosion vulnerability due to ocean phenomenon. Sea wave is one of the phenomenon that affect coastal vulnerability. Since in general sea wave measurement data is very hard to find, numerical modelling of the sea wave is an alternative method to provide sea wave data, as it is carried out in this research. Required data for this modelling process are bathymetry and wind data. These data are used as input for sea wave modelling using SWAN (Simulating Waves Nearshore). The sea wave characteristics produced from this modelling are wave statistics parameters such as significant height, period and direction of sea wave. Sensitivity analysis is needed to test the sensitivity of parameters to the result. The input parameters in this sensitiviy test include total grid, wind velocity, physical condition and time step. The sea wave model results are used to identify the vulnerability of Cirebon coastal area. Based on the result, the maximum significant wave height on the east monsoon period is 0,616 m with direction to the west and northwest. While on the west monsoon period the maximum significant wave height is 0,744 m with direction to the south and southeast. Based on sea wave chacracteristic obtained from modelling, Kecamatan Lemahwungkuk is the less vulnerable area to coastal erosion. Whereas Kecamatan Kapetakan, Suranenggala, Gunung Jati, Kejaksaan, Mundu, Astanajapura, Pangenan, Gebang and Losari are the most vulnerable areas to coastal erosion.